Disagreement: Sociolinguistic Investigations in Conversations - qizi, Nusratullaeva Shokhista Sabirjon (International Journal on Human-Computing Studies, 2023)
The article describes issues based on features of disagreement in language context, national and sociolinguistic features of this process in conversations. Linguistic phenomena reflect the facts of the social life of a given speaking community. The linguistic picture of the world reflects reality through the cultural picture of the world. Therefore, the study of a foreign language as a means of communication is inextricably linked with the study of the social and cultural life of countries and peoples who speak this language. When it comes to communication, especially intercultural communication, it can be very difficult to draw a line between the sociological and psychological aspects of communication. Both those and others deal with complex categories arising in the process of communication or transmitted through it - values, motives, attitudes, stereotypes and prejudices. And all these categories directly affect the communicative behavior of a particular linguistic personality.